2001
DOI: 10.1034/j.1600-0765.2001.360306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on bone formation induced by recombinant human bone morphogenetic protein‐2 combined with fibrous collagen membranes at subperiosteal sites

Abstract: This study was designed to examine the effect of aging on bone formation induced by recombinant human bone morphogenetic protein-2 (rhBMP-2) combined with a fibrous collagen membrane (FCM). Implantation was done subperiosteally in bilateral palatal grooves in 34 male Wistar rats divided into three age groups: a 10-week-old group (10w group), a 30-week-old group (30w group) and a 70-week-old group (70w group). RhBMP-2-combined FCMs were implanted on the left palatal grooves as BMP-implanted sites (BMP site), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
3
26
0
3
Order By: Relevance
“…Our findings of a significantly greater percentage of new bone formation in younger patients relative to older ones following remodeling with cancellous block-allograft in the anterior atrophic maxilla and posterior atrophic mandible (Nissan et al, 2011d;Nissan et al, 2011e) agree with earlier studies of the effect of age on new bone formation (Fisher et al, 2010;Matsumoto et al, 2001;Rando, 2006;Tanuka et al, 1996;Walboomers et al, 2006). Following induction of injury to the tibia marrow cavity in a rat model, MicroCT and histomorphometry revealed a reduced response with an increase in age, suggesting that the restoration of normal tissue is age-dependent (Fisher et al, 2010).…”
Section: Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings of a significantly greater percentage of new bone formation in younger patients relative to older ones following remodeling with cancellous block-allograft in the anterior atrophic maxilla and posterior atrophic mandible (Nissan et al, 2011d;Nissan et al, 2011e) agree with earlier studies of the effect of age on new bone formation (Fisher et al, 2010;Matsumoto et al, 2001;Rando, 2006;Tanuka et al, 1996;Walboomers et al, 2006). Following induction of injury to the tibia marrow cavity in a rat model, MicroCT and histomorphometry revealed a reduced response with an increase in age, suggesting that the restoration of normal tissue is age-dependent (Fisher et al, 2010).…”
Section: Commentsupporting
confidence: 82%
“…Others also noted differences in the osteogenic properties of bone marrow-derived osteoblast-like cells by donor age (Walboomers et al, 2006). In a study of bone formation induced by recombinant human bone morphogenetic protein-2 in male Wistar rats, the total volume of newly formed bone declined with aging (Matsumoto, et al, 2001). The reasons for the age-related decline in tissue repair are not well understood.…”
Section: Commentmentioning
confidence: 99%
“…rhBMP-2 induced bone formation in rat models, but its effect declined with age. 157 In a mouse model, 158 rhBMP-2 induced bone formation; the observed bone mass increase was associated with an increase in MSCs numbers, osteogenic activity and proliferation, and a decrease in apoptosis. Similarly, systemically administered 125 I-BMP-6 increased bone volume and mechanical characteristics of both the trabecular and cortical bone, thereby improving microarchitecture and quality of the skeleton in osteoporotic rats.…”
Section: Evidence For Potential Usefulness Of Bmps As Anabolic Therapmentioning
confidence: 99%
“…BMP-2 was also recently recognized as an osteoporosis-associated gene by human polymorphism studies (49). Animal studies have found that both gene expression and anabolic activity of BMP-2 are significantly decreased in aging bones (11,29,31,50,58). These results suggest that BMP-2 gene expression is necessary for maintenance of postnatal bone formation, particularly during aging, and that progressive, age-related loss of BMP-2 function may be one of the molecular mechanisms involved in the development of osteoporosis.…”
Section: :6197-6208 2006) Microtubule Inhibition Blocked ␤-Trcp-mmentioning
confidence: 99%
“…Microtubule inhibition had no effect on canonical Wnt VOL. 29,2009 INHIBITION OF MICROTUBULE ASSEMBLY STIMULATES BMP-2 1293…”
Section: Inhibition Of Microtubule Assembly Upregulates Bmp-2 Expressmentioning
confidence: 99%